1999
DOI: 10.1002/(sici)1096-8644(199911)110:3<243::aid-ajpa1>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation is an indicator of Austronesian influence in Island Melanesia

Abstract: Past studies have shown a consistent association of a specific set of mitochondrial DNA 9 base pair (bp) deletion haplotypes with Polynesians and their Austronesian-speaking relatives, and the total lack of the deletion in a short series of New Guinea Highlanders. Utilizing plasma and DNA samples from various old laboratory collections, we have extended population screening for the 9-bp deletion into "Island Melanesia," an area notorious for its extreme population variation. While the 9-bp deletion is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 15 publications
5
37
1
1
Order By: Relevance
“…In addition, there may have been a dis-proportionate amount of non-Polynesian male mediated gene flow, compared to females, from Melanesian related populations following initial settlement. Thus, in contrast to most of mtDNA and linguistic data [Merriwether et al, 1999;Gray and Jordan, 2000], the scenario suggested here by Y-chromosome variation is more consistent with a deep genetic contribution of Melanesian ancestry to the Polynesian gene pool than with the "Express Train to Polynesia" model.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In addition, there may have been a dis-proportionate amount of non-Polynesian male mediated gene flow, compared to females, from Melanesian related populations following initial settlement. Thus, in contrast to most of mtDNA and linguistic data [Merriwether et al, 1999;Gray and Jordan, 2000], the scenario suggested here by Y-chromosome variation is more consistent with a deep genetic contribution of Melanesian ancestry to the Polynesian gene pool than with the "Express Train to Polynesia" model.…”
Section: Discussioncontrasting
confidence: 61%
“…These migrations are a part of the overall colonization of Austronesian Polynesia that started from Southeast Asia about 3,000-4,000 years ago. While much of the evidence pertaining to the origins of Polynesians is archeological and linguistic [Bellwood, 1978;Gray and Jordan, 2000], mitochondrial DNA evidence has provided an independent assessment that is consistent with a Southeast Asian Austronesian influence [Hertzberg et al, 1989;Murray-McIntosh et al, 1998;Merriwether et al, 1999]. A different scenario, recently suggested by Y-chromosome markers, indicates that Melanesian populations strongly influenced the Polynesian gene pool [Kayser et al, 2000;Capelli et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Melton et al (1998) further suggested that since the origin of the ''Polynesian motif'' can be traced to Taiwan, the island of Formosa may be the origin of the expansion. The genetic influence of these aboriginal groups from Formosa in Melanesia has also been supported by other mtDNA investigations (Merriwether et al 1999). Other mtDNA studies have suggested that the Indonesian archipelago may be the origin of the expansion some 17,000 years ago (Richards et al 1998).…”
Section: Introductionsupporting
confidence: 52%
“…The mitochondrial DNA (mtDNA) intergenic COII/tRNA Lys 9-bp deletion marker, present at high frequency in some Asian 15 and African 16 populations, is found at low frequencies in India and arose multiple times independently. [17][18][19] Based on a study of autosomal and mtDNA markers in eight Indian tribes speaking Austro-Asiatic, Dravidian or Tibeto-Burman languages, it was concluded that these different language groups represented distinct founding groups, with AustroAsiatic speakers being the most ancient inhabitants of the region.…”
Section: Introductionmentioning
confidence: 99%